Correlations between body surface, rectal temperatures and the average weight of broilers - Reis, Túlio Leite; Souza , Christiane Silva; Dilelis, Felipe; Soares, Pollianna Luciene da Silva; Silva, Pedro Henrique Ferreira da; Curvello, Fernando Augusto (Revista de Ciências Agroveterinárias, 2022)
Body temperature is one of the indicators of broilers’ susceptibility to thermal stress, which can compromise performance. This study aimed to evaluate correlations between both the surface and rectal temperatures, besides the average weight of broilers assessed in different ages. Temperatures of broilers’ back, breast, and rectum were evaluated, besides the average weight of broilers at 7, 14, 21, and 35 days old. One hundred birds were assessed for each evaluation age, and the variables were submitted to Pearson’s correlation analyses. The rectal temperature had a correlation with the breast one when the birds were evaluated at 7 and 14 days old. The average weight correlated only with rectal and breast temperatures at 14 and 21 days old, respectively. The correlations between the temperatures were weak or insignificant in most of the studied ages. Therefore, the skin temperature is not a suitable parameter for measuring broilers’ temperature compared to the rectal one, so the use of infrared thermometer did not prove to be a useful strategy to estimate the internal temperature of broilers.